The importance of continuing professional development to career satisfaction and patient care: Meeting the needs of novice to mid- to late-career nurses throughout their career span - Sheri Price; Carol Reichert (Administrative Sciences, 2017)
This paper provides insights into the role of ongoing training and education on nurses' career satisfaction across different career stages and their ability to provide quality patient care. Eighteen focus groups were conducted over the course of five months in 2015 (January to May) in eight Canadian provinces. There were a total of 185 focus group participants. Each focus group lasted approximately 1.5 h and included 8-15 participants who self-selected in one of three distinct career stages (students, early-career, mid- to late-career). A thematic analysis of the data revealed that ongoing professional development is an expressed need and expectation for nurses across the various career stages. Student and early-career nurses expected sufficient training and education to facilitate workplace transitions, as well as continuing education opportunities throughout their careers for career laddering. For mid- to late-career nurses, the importance of lifelong learning was understood within the context of maintaining competency, providing quality patient care and enhancing future career opportunities. Training and education were directly linked to nurses' career satisfaction. Healthy work environments were identified by nurses as those that invested in continuing professional development opportunities to ensure continuous growth in their practice and provide optimal quality patient care. Training and education emerged as a cross-cutting theme across all career stages and held implications for patient care, as well as retention and recruitment.
Keywords: 350; intergenerational issues; professional development; retention and recruitment